Puerto Ricanness and Americanness: developing bicultural identity in Quiara Alegría Hudes’s memoir “My Broken Language” - Martynuska, Małgorzata (Respectus Philologicus, 2026)
This article analyses how the notion of language serves as a framework for illustrating the development of bicultural identity in Quiara Alegría Hudes’s memoir My Broken Language (2021). Firstly, the analysis illustrates Hudes’s determination to separate English and Spanish, which leads to her acceptance of her bicultural identity and the development of a unique variety of Spanglish. Secondly, the text investigates how acceptance of biculturalism parallels explorations of Hudes’s ethnic culture, with its traumatic history, and how this leads to manifestations of cultural heritage. The article demonstrates that biculturalism as an approach to acculturation varies across generations. While the first generation of Puerto Ricans in the USA tends to retain their indigenous culture and native language, the second generation develops a bicultural identity combining Puerto Ricanness and Americanness.
Keywords: Puerto Ricanness; Americanness; biculturalism; identity; Spanglish